Lung Ultrasonography as an Accurate Diagnostic Method for the Diagnosis of Community-Acquired Pneumonia in the Elderly Population. Issue 2 (June 2020) - Buda, Natalia; Hajduk, Adam; Jaworska, Joanna; Zdrojewski, Zbigniew
Abstract : Abstract: Community-acquired pneumonia (CAP) is one of the most common causes of both hospitalization and death in elderly patients. The chest x-ray (CXR) is nowadays still the imaging method of choice for patients suspected of having pneumonia. However, the sensitivity of CXR, particularly bedside chest radiography, is relatively low. Chest computed tomography, the procedure of higher precision, cannot be conducted routinely for safety, organizational, and economic reasons. Thus, lung ultrasonography (LUS) could be the most accurate diagnostic tool for CAP in the geriatric population. This prospective observational study involving 191 elderly patients (older than 65 years), hospitalized because of suspicion of pneumonia, aimed at comparing the diagnostic accuracy of LUS and CXR to final clinical diagnosis. During the first hours of hospitalization, both CXR and LUS were conducted. At discharge, pneumonia diagnosis was confirmed in 115 patients (60.2% of the study group). Chest x-ray revealed inflammatory lesions in only 65 patients (34% of the study group, 56.5% of the patients with final pneumonia diagnosis), whereas LUS was positive in 114 patients (59.7% of the study group, 99% of the patients with final pneumonia diagnosis). Sensitivity and specificity of LUS in pneumonia diagnosis were, respectively, 99% and 98.7%, whereas CXR sensitivity and specificity were 56.5% and 100%, respectively. The positive and negative predictive values of LUS were 99% and 98.7%, whereas, for CXR, they were 100% and 60.3%, respectively. Lung ultrasonography proved to be more effective at revealing pulmonary inflammatory lesions as compared with CXR in elderly patients suspected of pneumonia.